Does the direction of shapes and bodies influence the aesthetic perception of stage setups in dance? - Marisa Kempe (Termedia Publishing House, 2024)
Purpose Perceiving aesthetics in watching dance is a complex field of research, yet the component of space in general and stage setups, in particular in dance, is rarely studied. This study investigates the space on stage through the stage setups used in dance competitions. The main goal was to explore the aesthetic preferences of symmetry and the front-facing direction of shapes in a dance presentation. The investigation tries to determine how observers with differing dance experiences perceive the aesthetics of V-setups, diagonal lines, and their involved dancers by mirroring and turning shapes and bodies. Methods Categorised into three groups (modern dancers, other dancers, non-dancers), 72 active female participants from dance studios and college sports courses evaluated the perceived aesthetics of eight arranged stage setups through a video ranking. Nine motion-captured avatars performed the hip-hop bounce movement in each setup. The participant's task was to rank the presented stage setups based on their aesthetic perception. The ranking was illustrated with the means values, and the 5% significance criterion was tested with the Friedman-ANOVA. Results The stage setups are perceived differently by the observers. The V-setups reached higher aesthetic scores than the diagonal lines. Only the group of modern dancers showed no preference for the V versus the diagonals. There was a significant difference between the direction of the arranged dancers on stage. The setups with all dancers' bodies front-facing are aesthetically preferred. Furthermore, the regular V-setup with its top to the front and with all dancers' bodies facing the front achieved the highest score in the aesthetic evaluation. Conclusions The results provide evidence that the feature of symmetry is a driving factor in perceiving aesthetics in dance. The V-setup can be suggested for use in dance choreographies to improve the aesthetic value of observers. Also, the direction of the dancers facing the front is recommended and should be used in dance stage setups.